Lexical and grammatical features of Ugandan English - Isingoma, Bebwa (English Today, 2014)
English plays an important role in the lives of Ugandans. For example, official government records are written in English, Parliament conducts its business in English, national newspapers are written in English. English is the medium of instruction from elementary to tertiary level. English is a lingua franca among people of different ethnic groups whose mother tongues are mutually unintelligible, especially if they cannot use Luganda or, to some extent, Swahili. Most Ugandans learn English at school. Whereas the principles of English language teaching and learning in the Ugandan school syllabuses are purportedly drawn from Standard English (henceforth StE), deviations in everyday usage are unquestionably visible. Hence, as Fisher (2000: 61) puts it, the variety of English spoken in Uganda has been ‘indigenized’. Apart from featuring prominently in spoken discourse, Ugandan English (henceforth UgE) is also noticeable in Ugandan print media, official documents, and even in books written in Uganda. We should note that while there are significant pronunciation differences in UgE across the different regions in the country, Fisher (2000: 59) rightly contends that there are generally uniform grammatical and lexical features of UgE throughout the country.
Keywords: Grammatical features; Ugandan English